A language of resistance: The pro-Palestinian linguistic landscape of Cape Town (South Africa) and its physical, lingual, and functional complexity - Andrason, Alexander (Public Journal of Semiotics, 2026)
This article is dedicated to the pro-Palestinian linguistic landscape (PPLL) of Cape Town. An analysis of 239 signs reveals that the linguistic landscape of this research site is highly complex. The signage is diverse with regard to its physicality (modality, materiality, and compositionality), lingualism (languages used, their formal properties, and mutual configurations), and functionality (authorship, readership, purposes, domains of use, and thematic scope). Overall, the properties of the PPLL in Cape Town largely coincide with those characterizing the linguistic landscape of resistance in Palestine, particularly its street-art subtype. The two principal differences between Cape Town and Palestine concern the use of Arabic as a genuine resistance element in the landscape – absent in Cape Town but prominent in Palestine – and the incorporation of several local (South) African elements into the PPLL in Cape Town.